2009
DOI: 10.1262/jrd.20146
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Androgenetic Embryonic Stem Cells Differentiated to Multiple Cell Lineages in Three Embryonic Germ Layers <i>In Vitro</i>

Abstract: Abstract. The embryos of some rodents and primates can precede early development without the process of fertilization; however, they cease to develop after implantation because of restricted expressions of imprinting genes. Asexually developed embryos are classified into parthenote/gynogenote and androgenote by their genomic origins. Embryonic stem cells (ESCs) derived from asexual origins have also been reported. To date, ESCs derived from parthenogenetic embryos (PgESCs) have been established in some species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…While PG ES cell chimeras can survive postnatally with substantial contribution of ES cells (Sturm et al, 1994), AG ES cell chimeras typically exhibit severe defects and high lethality during fetal and postnatal stages (Mann et al, 1990;Narasimha et al, 1997). However, similar to ES cells derived from biparental (N) embryos, uniparental ES cells generate ecto-, meso-, and endodermal cell lineages in cell cultures including neural progenitor/stem cells and engrafting hematopoietic stem cells Eckardt et al, 2008;Eckardt et al, 2007;Lengerke et al, 2007;Teramura et al, 2009). We consider the analysis of AG ES cells relevant for two reasons: 1.)…”
Section: B C Dmentioning
confidence: 99%
“…While PG ES cell chimeras can survive postnatally with substantial contribution of ES cells (Sturm et al, 1994), AG ES cell chimeras typically exhibit severe defects and high lethality during fetal and postnatal stages (Mann et al, 1990;Narasimha et al, 1997). However, similar to ES cells derived from biparental (N) embryos, uniparental ES cells generate ecto-, meso-, and endodermal cell lineages in cell cultures including neural progenitor/stem cells and engrafting hematopoietic stem cells Eckardt et al, 2008;Eckardt et al, 2007;Lengerke et al, 2007;Teramura et al, 2009). We consider the analysis of AG ES cells relevant for two reasons: 1.)…”
Section: B C Dmentioning
confidence: 99%
“…In human gynogenetic pESCs, lack of expression from paternally expressed loci reveals their uniparental origin [47,48]. The argument has been made that some altered imprinting patterns may be tolerable for downstream regenerative medicine applications if the desired tissue does not express the loci in question [44,52]. The ability of mouse pESCs to reconstitute hematopoietic lineages, despite relaxed imprinting found in both gynogenetic and androgenetic-derived pESCs, supports this contention [53].…”
Section: Epigenetics and Regenerative Medicine Hescs Derived From Artmentioning
confidence: 99%
“…The ability of mouse pESCs to reconstitute hematopoietic lineages, despite relaxed imprinting found in both gynogenetic and androgenetic-derived pESCs, supports this contention [53]. However, there is common recognition of the need for further transplantation studies for comprehensive analysis of any safety issues which may be relevant to human regenerative medicine applications using pESCs [44,52].…”
Section: Epigenetics and Regenerative Medicine Hescs Derived From Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinger et al [20] observed widespread contributions from aESCs in fetal chimeric mice and reported that their neural differentiation potential, in terms of self-renewal properties of neural stem cells, did not differ from that of normal biparental fESCs [20]. In addition, aESCs are able to differentiate into various cell types of all three embryonic germ layers [21]. Together, homozygous ESCs, or at least pESCs, are indistinguishable from fESCs with respect to tissue/organ contribution.…”
Section: Mrna and Protein Expressionmentioning
confidence: 99%